(untitled) (Research, Society and Development, 2022)
This research, under laboratory condition, evaluated the efficiency of different strains of entomopatogenic fungus Beauveria bassiana to control leaf-cutting ant Atta sexdens rubropilosa. Soldiers and workers were inoculated with suspensions containing 1.0x107, 1.0x108, 1.0x109 and 1.0x1010 con mL-1 and maintained in B.O.D, at 25±1°C, 70% RH and 12 hours of photophase, without food. The mortality was evaluated daily, with 15 days after inoculation. Experimental design was entirely random. The sporulation data were submitted to the analysis of variance and the LT50 values (in days) were obtained through the Probit analysis. All strains of B. bassiana were pathogenic, being workers more susceptible than soldiers. The strains IBCB 21 and IBCB 07 caused high percentages of confirmed mortality showing potential for use in the control of A. sexdens rubropilosa. Strain IBCB 21 was more virulent for workers, whereas isolated IBCB 07 was more virulent for soldiers. Both isolates presented no significant difference among tested concentrations.